Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Oxidative potential of size-resolved PM related to water-soluble components and total and bioaccessible mass fractions of PAH derivatives - Athanasios Besis; Marco Wietzoreck; Eleni Serafeim; Benjamin A. Musa Bandowe; Stefanie Hildmann; Rong Jin; Jun-Tae Kim; Athanasios Kouras; Gerhard Lammel; Constantini Samara (Atmospheric Pollution Research, 2026)

Interannual variation in soil respiration and its components across cropland, grassland, and pasture in the agro-pastoral ecotone of Northern China - Deping Wang; Kun Zhao; Thomas A. Monaco; Sanling Jin; Yuping Rong (Agriculture, Ecosystems & Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Atmospheric deposition of chlorinated and brominated polycyclic aromatic hydrocarbons in central Europe analyzed by GC-MS/MS - Rong Jin; Benjamin A. Musa Bandowe; Minghui Zheng; Guorui Liu; Barbora Nežiková; Roman Prokeš; Pavel Čupr; Jana Klánová; Gerhard Lammel (Environmental Science and Pollution Research, 2021)
Chlorinated and brominated polycyclic aromatic hydrocarbons (ClPAHs and BrPAHs) are persistent organic pollutants that are ubiquitous in the atmospheric environment. The sources, fate, and sinks in the atmosphere of these substances are largely unknown. One of the reasons is the lack of widely accessible analytical instrumentation. In this study, a new analytical method for ClPAHs and BrPAHs using gas-chromatography coupled with triple quadrupole mass spectrometry is presented. The method was applied to determine ClPAHs and BrPAHs in total deposition samples collected at two sites in central Europe. Deposition fluxes of ClPAHs and BrPAHs ranged 580 (272–962) and 494 (161–936) pg m −2 day −1 , respectively, at a regional background site, Košetice, and 547 (351–724) and 449 (202–758) pg m −2 day −1 , respectively, at a semi-urban site, Praha-Libuš. These fluxes are similar to those of PCBs and more than 2 orders of magnitude lower than those of the parent PAHs in the region. Seasonal variations of the deposition fluxes of these halogenated PAHs were found with maxima in summer and autumn, and minima in winter at Košetice, but vice versa at Praha-Libuš. The distribution of ClPAHs and BrPAHs between the particulate and dissolved phases in deposition samples suggests higher degradability of particulate BrFlt/Pyr and BrBaA than of the corresponding ClPAHs. A number of congeners were detected for the first time in the atmospheric environment.

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Genetic diversity and population structure of the northern snakehead (Channa argus Channidae: Teleostei) in central China: implications for conservation and management - Ruo-Jin Yan; Gui-Rong Zhang; Xiang-Zhao Guo; Wei Ji; Kun-Ci Chen; Gui-Wei Zou; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics, 2018)

Soluble overexpression and purification of bioactive human CCL2 in E. coli by maltose-binding protein - Thu Trang Thi Vu; Bon-Kyung Koo; Jung-A Song; Seon-Ha Chong; Cho Rong Park; Minh Tan Nguyen; Boram Jeong; Han-Bong Ryu; Jae Young Seong; Yeon Jin Jang; Robert Charles Robinson; Han Choe (Molecular Biology Reports, 2015)

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

Aneuploidy and chromosomal instability: a vicious cycle driving cellular evolution and cancer genome chaos - Tamara A. Potapova; Jin Zhu; Rong Li (Cancer and Metastasis Reviews, 2013)

The complete mitochondrial genome of Spilonota lechriaspis Meyrick (Lepidoptera: Tortricidae) - Jin-Liang Zhao; Yan-Yan Zhang; A-Rong Luo; Guo-Fang Jiang; Stephen L. Cameron; Chao-Dong Zhu (Molecular Biology Reports, 2011)